Cheilostome bryozoan Hippoporina indica (Pillai, 1978), from Colombo Port: A new record - Marasinghe, M.M.K.I.; Ranatunga, R.R.M.K.P.; Anil, A.C.; Weerasinghe, R.L. (Proceedings of die Twenty second Scientific Sessions of the Sri Lanka Association for Fisheries and Aquatic Resources, 20th May 2016. Auditorium of National Aquatic Resources Research and Development Agency, Colombo IS, Sri Lanka., 2016)
Attached
Keywords: Hippoporina indica; encrusting bryozoan; Colombo Port; marine biofouling